Pengaruh Pendidikan Kesehatan Tentang Pijat Bayi Terhadap Pengetahuan Dan Sikap Ibu Dalam Memijat Bayi Secara Mandiri - Paninsari, Debora; Juwita, Norma; Malasari, Novi; Purba, Novita Bintara (Innovative: Journal Of Social Science Research, 2024)
In Indonesia, the role of baby massage in village communities is still played by the dukun. So far, massage is not only done when babies are healthy, but also when babies are sick or fussy and has become a routine for baby care after birth. The aim of this research was to determine the effect of health education about baby massage on mothers' knowledge and attitudes in massaging babies independently at the Labu Beach Community Health Center. The type of research used is quasi-experimental with one-group intervention. The population in this study were 23 primiparous mothers who had babies aged 0-6 months at the Labu Beach Community Health Center. The sampling technique was total sampling of 23 people. The type of data used in this research is primary and secondary data with a questionnaire instrument. Analysis of research data was univariate and bivariate analysis using the Wilcoxon test. The research results showed that the majority of mothers' knowledge before being given health education was lacking at 20 people (87%), and the minority was sufficient at 3 people (13%). The majority of mothers' knowledge after being given health education was good as many as 15 people (65.2%), and the minority was poor as many as 8 people (34.8%). The majority of mothers' attitudes before being given health education was negative as many as 13 people (43.5%), and the minority was positive as many as 10 people (13%). The majority of mothers' attitudes after being given health education were positive, 20 people (87%), and a negative minority, 3 people (13%). There is an influence of health education about baby massage on mothers' knowledge of massaging babies independently with a p value of 0.002. There is an influence of health education about baby massage on mothers' attitudes towards massaging babies independently with a P value of 0.000.